HALAL INDUSTRY: RELIGION AND ECONOMY - Niswa, Harisatun; Nur Diana, Ilfi; Yuliana, Indah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Recently, the halal industry has become a world trend. This is proven by the prospect of the halal industry, which continues to grow from year to year. Halali industry when viewed from a religious aspect gives an understanding that the label "halal" which is attached to the industrial dwarf does not only become a pseudo identity. This research aims to understand the labeling of halal industry from religious and economic aspects. The method used is literature review. The results of this study indicate that the halal industry in the religious aspect is one of the uses of the name "halal" in popularizing the industry that is currently being undertaken and in the economic aspect it contributes to the effectiveness of the national economic development.